Colloidal Silver (CS) as an Antiseptic: Two opposing viewpoints - Cock, I.E.; Mohanty, Shimony; White, Alan; Whitehouse, Michael (Pharmacognosy Communications)
Introduction: Despite its long history as an antiseptic, the image of CS has been badly ‘tarnished’ by opportunistic promoters, lack of quality controls (QC), deliberate misinformation and reprehensible scare tactics. This article evaluates some commercial colloidal silver (CS) preparations for their efficacy as antiseptic agents. Aims: We examined the potential medicinal value of commercially available CS preparations testing them by a) various chemical and physical criteria and also b) in vitro assays for bio-efficacy and safety. Methods: Antibacterial activity of CS preparations was determined by disc diffusion growth inhibition assays against a panel of pathogenic bacteria and fungi. Toxicity (LC50) was assessed by the Artemia franciscanna nauplii bioassay. Results: Of the 12 CS preparations tested, 10 (83%) showed antimicrobial activity, albeit with varying specificity and efficacy. Argyrol and HLY displayed the broadest specificity, inhibiting the growth of all 14 bacteria tested (100%). These particular preparations also inhibited the growth of 3 (100%) and 2 (67%) of the fungal species tested respectively. The other preparations had varying degrees of efficacy and specificity. In general, only low concentrations of CS were required to achieve antibiotic activity, with MIC values ≤ 5µg/ml for some preparations against some microbial species. In contrast, 2 colloidal gold preparations were completely devoid of antimicrobial activity. All CS preparations were either nontoxic or displayed low toxicity in the Artemia franciscanna nauplii bioassay, further confirming their potential as antiseptics for medicinal use. Conclusions: The commercial CS preparations varied widely in their potential utility as complementary medicines. The establishment of quality controls for both antimicrobial efficacy and incipient toxicity to animal cells are badly needed. However, this study does demonstrate the effective antiseptic activity of certain CS preparations indicating that they should be seriously considered as medicinals for topical use e.g. treating burns, periodontitis, thrush etc.
Keywords: silver nanoparticles; colloidal silver; inorganic pharmacognosy; antimicrobial; Ago; Ag+